Viral diseases in common bean crops in Argentina - Rodriguez Pardina, Patricia (Research Trends, 2021)
Common bean (Phaseolus vulgaris) is the most important legume for direct human consumption worldwide. Several factors can affect bean yield, with viral diseases being responsible for losses in crop productivity, especially in tropical and subtropical regions. In Argentina, 12 virus species have been identified: Bean common mosaic virus (BCMV), Cucumber mosaic virus (CMV), Alfalfa mosaic virus, Cowpea mild mottle virus (CpMMV), Southern bean mosaic virus (SBMV) and seven species of begomovirus. This review describes symptoms, etiology, as well as epidemiological and management aspects of viruses affecting bean crops in Argentina.